(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The article aims to examine the use of artificial intelligence by public administrations in a legal context characterized by the absence of general regulation and centered on the Courts ex post regulation. Starting from a case relating to a Ministry of Education’s plan based on an algorithm, it analyzes the effectiveness of the European Data Protection Regulation and the actual role of the “human in the loop” principle, considering the different types of algorithm applicable and the legal background and expertise of public officials operating with artificial intelligence.